Simulation Of Token Bucket Algorithm For Network Traffic Performance - Yusof, Robiah; Mat Nawi, Nor Afifah (Penerbit Universiti Teknikal Malaysia Melaka, 2020)
The internet isthe most important medium for users in the cyber world. Along with the development of internet technologies allows users to do multi-tasking,nonetheless, itinitiates collision.The traffic collision is one of the problems that occurred in the wired network. In order to provide a high-performance network, the quality-of-service (QoS) is required. Traffic shaping is one of the tools that can provide QoS in the network traffic. However, implementing the basic mechanism of traffic shaping cannot solve this issue. In this research, the optimal size of bucket in Token Bucket Algorithm(TBA)is used as one of the techniques in traffic shaping. The variables of this algorithm are modified in order to offer the effective proposed token bucket size that can be used in wired network and tested using OPNET modeler. This algorithm has successfully reduced the delay in the network traffic and improve the response time when users request several applications concurrently.